Hambatan komunikasi pasangan perkawinan antar budaya suku Pakistan – suku Melayu - Pramisdi Winanto Saputro (Universitas Tangerang Raya, 2023)
Interracial marriages in Indonesia often cause many problems and communication barriers, the provisions relating to marriage are regulated by the state. Marriage between Malays and Pakistanis is the theme of this thesis. In the existing laws and regulations in Indonesia, marriage is clearly regulated, especially in mixed marriages of different nationalities. But marriage here is more about barriers and also the communication process in married life. The research theory here draws more on theories of behavior and cross-cultural communication. This is due to the existence of two or more legal systems used. Differences in the legal basis used and differences in interpreting the law are the main problems and communication barriers in mixed marriages. Departing from these problems, the author is interested in conducting research, with three problem formulations, namely (1) How do communication barriers from mixed marriages affect the life process ; (2) What are the research methods and data collected in this research; (3) What is the conclusion about communication barriers. The conclusion of this research is the resolution of communication barriers that arise from cross-cultural marriages between Malays and Pakistanis within the institution of marriage. Including the ins and outs of the differences between the two, and how to deal with communication barriers in marriage, even though there are several obstacles, there are always solutions and make the marriage relationship harmonious until now.